Representasi Kisah Percintaan Di Era Milenial Dalam Film Bad Boys Vs Crazy Girls - Desi Naili Rahmadawati; Indria Indria; Anis Endang Sri Murwani (Jurnal Multidisiplin Dehasen (MUDE), 2023)
This study aims to determine the Representation of Romance in the Millennial Era in the Film Bad Boys vs Crazy Girls, this research is a qualitative study using the data analysis technique used by researchers is Roland Barthes semiotics, the results of this study show that films as one of the community's favourite entertainment facilities are always interesting and there are many messages that can be taken. One of them is the film Bad Boys vs Crazy Girls, namely Sign and Code (signs and codes) contained in the meaning of Representation of Romance in the Millennial Era, the denotation in this story is initially Liam and Kate, two of the most popular students in school who hate each other then over time they have the same feeling of falling in love until finally Kate and Liam are dating. Furthermore, the connotation in this film changes from hating each other to loving each other which describes a journey that usually occurs in romance stories, then the myth in this film is that someone who hates each other with the passage of time who is always together will cause feelings of love. The selection of signs and codes focuses on the scene of Liam and Kate falling in love again. Through semiotic studies, researchers at least find signs and codes that are significant to the research objectives in the scenes of teenage life summarised in the denotation and connotation tables.